2018
DOI: 10.1061/(asce)mt.1943-5533.0002491
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of High-Strength Polypropylene Fiber-Reinforced Self-Compacting Concrete Exposed to High Temperatures

Abstract: The utilization of structural high-performance concrete reinforced with polypropylene fibers in applications demanding long exposure times to high temperatures, such as in case of thermal energy storage systems, is analyzed in this work. Different temperatures: 100, 300, 500 and 700°C (hot), as well as cooled-down states (cold) and different exposure times (6, 24 and 48 h) have been analyzed. The thermogravimetric analysis, fracture behavior, compressive strength, the Young's modulus and tensile strength of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…e fiber used in this study is polypropylene fiber with physical characteristics as shown in Table 2 (provided by the manufacturer). In accordance with the relevant literature [5,[13][14][15] and the actual applications of retaining structure, we designed 4 different polypropylene fiber contents (i.e., 0%, 0.2%, 0.4%, and 0.6%) and studied their dynamic performance, respectively.…”
Section: Sample Preparation and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…e fiber used in this study is polypropylene fiber with physical characteristics as shown in Table 2 (provided by the manufacturer). In accordance with the relevant literature [5,[13][14][15] and the actual applications of retaining structure, we designed 4 different polypropylene fiber contents (i.e., 0%, 0.2%, 0.4%, and 0.6%) and studied their dynamic performance, respectively.…”
Section: Sample Preparation and Designmentioning
confidence: 99%
“…Meanwhile, polypropylene fiber reinforced concrete is able to suppress the generation of early shrinkage cracks to a certain extent so as to improve the ductility of concrete. At present, polypropylene fiber reinforced concrete has been widely concerned and applied in engineering structures, such as dams, retaining walls, and culverts [1][2][3][4][5]. In actual engineering projects, concrete structures are subjected to not only static actions but also dynamic actions including earthquake, collision, and explosion.…”
Section: Introductionmentioning
confidence: 99%
“…The booming infrastructure activities along “The Belt and Road” line, especially in the areas with an extreme environment like saline-alkali soil, tjaele, island, and high daily temperature variation, require more application of advanced polymer fiber-reinforced composites to overcome the effect of the harsh natural environment on the duration of infrastructure materials. Polypropylene (PP) fiber has become an attractive option for application in extreme conditions due to its chemically inert, appropriate thermal properties, low weight, high specific strength, hydrophobia, and low cost [ 1 , 2 , 3 ]. However, disadvantages including weak interfacial adhesion between fibers and matrix, smooth surface, and low modulus of elasticity all need to be improved to meet the application of fibers in extreme conditions.…”
Section: Introductionmentioning
confidence: 99%
“…So, reuse or recycling of plastic waste is preferred. plastic waste utilization in the concrete instead of fine aggregate has been studied by many researchers during the last years [1][2][3][4][5][6][7]. In 2012, Rai et al carried out an experimental study focused on a plastic waste addition with ratios of (0%, 5%, 10%, and 15%) to normal concrete as a partial replacement of the sand with and without superplasticizer.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The researcher noticed the optimum content of plastic waste (HDPE) is 2 % for solid blocks and 4% of paver block with marginal decreasing in compressive strength. Rois et al examined the useing of high performance structural concrete reinforced by polypropylene fibers in thermal energy storage systems [5]. These systems are susceptible for long exposition time at high temperatures, the behavior of the concrete at varying temperatures (hot tests) with (100°C, 300°C, 500°C, 700°C), cooled-down states (cold tests) and exposition times (6, 24,48) hour were a parametric.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%